A review of phase change materials in asphalt binder and asphalt mixture. (20th October 2020) - Guo, Meng; Liang, Meichen; Jiao, Yubo; Zhao, Wei; Duan, Yongxia; Liu, Haiqing
Highlights: PCM can regulate the pavement temperature by releasing or absorbing heat. The leaked PCM will chemically react with asphalt and effect its performance. PCM can improve high-temperature stability and crack resistance of asphalt mixture. The synthesis process of CPCM still needs to be explored to reduce PCM losses. Abstract: Phase change materials (PCMs) can adjust the external temperature by changing their phase states. In order to understand the application of PCMs in asphalt pavements, this paper mainly studied the classification, mechanism, thermoregulation effects of PCMs and the preparation method of composite phase change materials (CPCMs). In addition, the effects of directly incorporated PCMs and composite ones on the properties of asphalt binder and asphalt mixture were described. Results show that directly incorporated PCMs play a role in thermoregulation. However, there is high temperature leakage phenomenon, which has a significant adverse effect on the road performance of asphalt binder and asphalt mixture. CPCMs effectively prevented leakage, reduced the adverse impact on the physical properties of asphalt binder. It is an ideal way to add CPCMs as an alternative component to asphalt mixture. CPCMs improved the heat storage and release capacity of asphalt mixture and the road performance of asphalt mixture, such as high-temperature stability, low-temperature anti-cracking had been improved.